Composite and bi-layer films based on gelatin and chitosan - Rivero, Sandra G. M. (2009)
The aims of this work were: to develop composite, bi-layer and laminated biodegradable films based on gelatin and chitosan, to determine film barrier and mechanical properties and to characterize their microstructure. Gelatin and chitosan concentrations used were 7.5% and 1% (w/w), respectively. Glycerol (0.75%) was added as plasticizer. Physicochemical properties such as moisture content, transparency and color were analyzed. Composite and bi-layer systems showed a compact structure indicating a good compatibility between components. Water vapor permeability (WVP) was independent of film thickness up to 120 μm for gelatin films and 60 μm for chitosan ones. Both, bi-layer and laminated systems resulted effective alternatives to reduce WVP of composite films (at least 42.5%). Bi-layer systems showed better mechanical properties than laminated ones. The resistance at break increased from 54.3 for composite to 77.2 MPa for bi-layer films, whereas elongation at break values of both composite and bi-layer films were similar (2.2–5.7%).